# My final Diff Eq question for now

Here u(x,t) refers to D'ALembert's solution for the one dimensional wave. L represnets the legnth of the string and c, the speed of the wave.

Find u(3/4,2) where l=c=1 f(x) = x(1-x), g(x) = x^2 (1-x)
Ok i know that from earlier that i ahve to extend g as an even periodic function over this interval

But what about f? Does f have to be extended ?

For teh extension of g... Do i simply move that function to right?
so $$g_{1} (r) = r^2 (1-r)$$

for $$g_{2} (r) = (-r-\frac{1}{2})^2)[1-(-r-\frac{1}{2})]$$ over the interval [5/4,7/4]

and finally $$g_{3} (r) = (r-1)^2)[1-(r-1)]$$ over the interval [7/4,2]

am i going in the right direction??

Simialr question i have is
If $f(x) = x^2 (1-x)^2, g(x) = 1, \partial u/ \partial x (0,t)=0, c=1, find u(3/4,7/2)$

does f(x) have to be extended
if so would it be extended by a polynomial of degree 4? in which case
for [1,2] (x-1.5)^4
for [2,3.5] (2.5-x)^4 [/tex]

your help would be greatly appreciated!
p.s. the other question was not required to be answered tahts why you dont see that one, thanks!

Last edited:

saltydog
Homework Helper
Stunner, the extensions depend on the boundary conditions: if the boundary conditions are of a form u(0,t)=0 or u(L,t)=0 then odd-extend about those points. If the boundary conditions are of the form $u_x(0,t)=0$ or $u_x(L,t)=0$, then even-extend about the points. If the left boundary is u(0,t) then odd-extend about that point and if the right boundary is $u_x(L,t)=0$, then even-extend about that point.

You don't state the boundary conditions above.

the first one is just like this question from earlier https://www.physicsforums.com/showthread.php?t=90027

the second one has the following conditions
$f(x) = x^2 (1-x)^2, g(x) = 1, \partial u/ \partial x (0,t)=\partial u/ \partial x (1,t)0, c=1$ find u(3/4,7/2)

ok to odd extend is for a function to follow this rules f(-x) = -f(x)
and to even extend is fora function to follow f(-x) = f(x)

i nthe first case i need to odd extend - but am right in what i have done?

in the second case i need to even extend

now heres the stupid part - how do i even or odd extend?

Last edited:
saltydog
Homework Helper
stunner5000pt said:
the first one is just like this question from earlier https://www.physicsforums.com/showthread.php?t=90027

the second one has the following conditions
$f(x) = x^2 (1-x)^2, g(x) = 1, \partial u/ \partial x (0,t)=\partial u/ \partial x (1,t)0, c=1$ find u(3/4,7/2)

Ok, the first one has boundary conditions:

u(0,t)=0 and u(L,0)=0

So then both f(x) and g(x) would be odd-extended about 0 and L. The second one has derivative boundary conditions so f(x) and g(x) for that one would be even-extended. Can you draw plots of both of these extensions?

the one on the left applies to the first one

te one of hte right applies to the second one

#### Attachments

saltydog
Homework Helper
Not exactly Stunner. You need to extend both f(x) and g(x) for each problem. Plots below are the odd-extensions for the first problem. First is odd-extension of f(x)=x(1-x), second one is the odd-extension for g(x)=x^2(1-x). Both are extended in the range of -5/4 to 11/4 which corresponds to the intervals needed in order to calculate the value for u(3/4, 2). Can you come up with the equations for each interval for each plot in order to plug it into D'Alembert's formula?

#### Attachments

ok so then for the first one
For f(x)
x(1-x) [0,1]
(x-1)(x-2) [1,2]
(2-x)(x-3) [2,3]

x(x+1) [-1,0]
(x+1)(x+2) [-2,-1]

for g(x)
x^2 (1-x) [0,1]
(x-2)^2 (-1-x) [1,2]
-x(x+1)^2 [-1,-2]

saltydog
Homework Helper
stunner5000pt said:
ok so then for the first one
For f(x)
x(1-x) [0,1]
(x-1)(x-2) [1,2]
(2-x)(x-3) [2,3]

x(x+1) [-1,0]
(x+1)(x+2) [-2,-1]

for g(x)
x^2 (1-x) [0,1]
(x-2)^2 (-1-x) [1,2]
-x(x+1)^2 [-1,-2]

This is what I get:

For f(x):

$$(-1,0)\Rightarrow \quad x(1+x)$$
$$(0,1)\Rightarrow \quad x(1-x)$$
$$(1,2)\Rightarrow \quad -(x-1)+(x-1)^2$$
$$(2,3)\Rightarrow \quad (x-2)-(x-2)^2$$

for g(x):

$$(-1,0)\Rightarrow \quad -x^2(1+x)$$
$$(0,1)\Rightarrow \quad x^2(1-x)$$
$$(1,2)\Rightarrow \quad -(2-x)^2[1-(2-x)]$$
$$(2,3)\Rightarrow \quad (x-2)^2[1-(x-2)]$$